Pontastacus leptodactylus (Eschscholtz, 1823) and Faxonius limosus (Rafinesque, 1817) as new, alternative sources of chitin and chitosan - Nuc, Zofia (2023)
The growing demand for chitin and chitosan makes it necessary to look for new sources of these polymers and to develop more environmentally friendly methods for their isolation. The subjects of the current study were chitin and chitosan extracted from shells of two crayfish species: P. leptodactylus and F. limosus. The obtained polymers were characterized by physicochemical properties (molecular weight, thermal stability, and structure). The obtained chitosan was evaluated regarding biocompatibility and antimicrobial activity. The yield of chitin obtained from P. leptodactylus and F. limosus with a standard method was 22 ± 2.7% and 20 ± 3.6% (w/w), respectively (a preliminary extraction with a natural deep eutectic solvent was performed successfully only for P. leptodactylus). The yield of chitosan production was 15 ± 0.3% and 14 ± 4.2%, respectively. Both chitosan samples showed antimicrobial activity against E. coli and S. aureus. Cytotoxicity assays revealed a time- and concentration-dependent effect, with a milder impact at concentrations up to 250 µg/mL. A more favourable profile was observed for chitosan from F. limosus shells.